Gene doping: Biomedical and laws aspects of genetic modification of athletes - Santamaria, S.; Ascione, A.; Tafuri, D.; Mazzeo, F. (Medicina Sportiva, 2013)
The desire to increase their own physical performances in order to obtain better results in sports led athletes to seek alternative methods to train hard. In the time, the results obtained in genetics have been used in the field of sport, creating a new form of doping: "gene doping". The athletes may be able to use gene therapy to re-engineer their bodies for better performances. In the sport, leading authorities predict that the genetic engineering of athletes will be widespread by the 2004 Olympics. This new type of doping can be dangerous and detrimental to health as with it, gene transfer vectors may be produced in non-controlled laboratories. It is really difficult to identify athletes who have resorted to gene doping because many of the muscle based gene technologies are unlikely to be detected by urine or blood tests. Various options have been advanced to detect the use of genes for the purpose of doping but they turn out to be too invasive and not easily achievable. Athletes are not fully aware of the physical problems associated with the use of gene doping and they and their supporting staff will be educated on this subject in order to prevent the use.